2000
DOI: 10.1046/j.1365-2362.2000.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Late diagnosis of Kawasaki disease is associated with haptoglobin phenotype

Abstract: Patients with Hp 2-1 have patterns of delayed or incomplete presentation of clinical symptoms. Therefore, the late diagnosis of KD is associated with haptoglobin phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Several previous studies reported increased levels of certain cytokines or cytokine regulators in association with KD, 13,[18][19][20][21] and a haptoglobin phenotype that may help in diagnosis at a late stage has been identified. 25 Although we confirmed the elevation of IL-6 levels compared with healthy controls, this marker was not as specific or sensitive of a predictor of KD when compared with IP-10 because of lack of discrimination in the suspected cases with fevers ( Figure 1). Although IL-1β was critical in the development of coronary lesions in a mouse model of KD 26 , the plasma levels of IL-1β were not significantly elevated in the patients with acute KD in the present study (Figure 1).…”
Section: Discussionmentioning
confidence: 56%
“…Several previous studies reported increased levels of certain cytokines or cytokine regulators in association with KD, 13,[18][19][20][21] and a haptoglobin phenotype that may help in diagnosis at a late stage has been identified. 25 Although we confirmed the elevation of IL-6 levels compared with healthy controls, this marker was not as specific or sensitive of a predictor of KD when compared with IP-10 because of lack of discrimination in the suspected cases with fevers ( Figure 1). Although IL-1β was critical in the development of coronary lesions in a mouse model of KD 26 , the plasma levels of IL-1β were not significantly elevated in the patients with acute KD in the present study (Figure 1).…”
Section: Discussionmentioning
confidence: 56%
“…Haptoglobin, an acute-phase protein synthesized by the liver in response to inflammatory cytokines, has been seen in association with vascular disease [2, 3]. The haptoglobin 2–1 phenotype has been reported in association with incomplete KD [9]. …”
Section: Discussionmentioning
confidence: 99%
“…IVIG resistance with persistent or recrudescent fever occurs in approximately 18 % of KD patients. Retreatment involved more individual adjustment, consisting of intravenous steroid pulse therapy, infliximab, cyclophosphamide, anakinra, etanercept, methotrexate, or plasmapheresis [ 1 , 4 6 ]. Additionally, antioxidants, as vitamin C, and drugs affecting cholesterol levels, can reduce endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%